2016
DOI: 10.3892/mmr.2016.5127
|View full text |Cite|
|
Sign up to set email alerts
|

Silencing of RTKN2 by siRNA suppresses proliferation, and induces G1 arrest and apoptosis in human bladder cancer cells

Abstract: Human bladder cancer is the most common urological malignancy in China. One of the causes of carcinogenesis in the cancer may be gene mutation. Therefore, the present study investigated the expression levels of Rhotekin 2 (RTKN2), a Rho effector protein, in human bladder cancer tissues and cell lines, and examined the effect of RTKN2 on the proliferation, cell cycle, apoptosis and invasion of human bladder cancer cell lines. The mRNA expression levels of RTKN2 in 30 human bladder cancer tissue samples were sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Previous studies have confirmed the anti-apoptotic effects of RTKN2 on several cancer types including HCC and bladder cancer ( 5 , 6 ). Consistent with these observations, the results of the present study demonstrated that silencing of RTKN2 markedly induced the apoptosis of human colon cancer cells.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Previous studies have confirmed the anti-apoptotic effects of RTKN2 on several cancer types including HCC and bladder cancer ( 5 , 6 ). Consistent with these observations, the results of the present study demonstrated that silencing of RTKN2 markedly induced the apoptosis of human colon cancer cells.…”
Section: Discussionmentioning
confidence: 64%
“…Wei et al ( 5 ) reported the overexpression of RTKN2 in the majority of hepatocellular carcinoma (HCC) patients and demonstrated an association between RTKN2 expression and proliferation, apoptosis and metastatic progression. Similarly, Liao et al ( 6 ) reported the anti-apoptotic effects of RTKN2 in bladder cancer cells. Furthermore, the overexpression of RTKN2 reduced viability and increased sensitivity to 25-OHC ( 7 ), which is directly associated with apoptosis in hematopoietic and leukemic cells ( 8 10 ).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Therefore, the reduction of BCL2L15 may be involved in this effect. Silencing of RTKN2 suppressed proliferation and induced apoptosis and cell cycle arrest in human bladder cancer cells (Liao et al, ). RTKN‐mediated NFκB activation confers resistance to apoptosis in gastric cancer (Liu, Wang, Chi, Wu, & Chen, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the reduction of BCL2L15 may be involved in this effect. Silencing of RTKN2 suppressed proliferation and induced apoptosis and cell cycle arrest in human bladder cancer cells (Liao et al, 2016).…”
Section: Data Verification By Real-time Pcrmentioning
confidence: 98%